An Assessment of the Factors Affecting Cause - Enjoined Marketing Offerings and its Impact on Consumer Behavior - Gupta, Shruti (Indian Journal of Marketing, 2023)
Despite the ever-escalating adoption of cause-related marketing, making it a crucial ingredient of the marketing endeavor, many companies are seen embracing the same to gain an enduring competitive advantage among consumers today. This has, in turn, led practitioners and academicians alike to investigate the consumer reaction to it. This study aimed at assessing and investigating the impact of various demographic and psychological factors, as identified, pertaining to consumers’ choice response in the context of customer relationship management (CRM) offerings in India. Aliterature review followed by a semistructured interview with 20 people falling in the age bracket of 25 – 58 years on attitude and purchase intention was undertaken. This was followed by a detailed questionnaire-based quantitative study wherein 390 respondents responded to the questionnaire personally, while 170 were contacted through an online medium. Factor analysis was adopted to extract the psychographic factors affecting consumer choice. The effect of the same was assessed with respect to attitude toward the same using the multiple hierarchical regression model. The study provides valuable discernment and significant connotations for academicians and marketers alike.